Methods, Techinques and Researchers. Methodological Reflections on the Study of Disability - Pretto, Albertina (Espacio Abierto, 2018)
The article aims to offer some reflections and considerations arising from a case study regarding people with physical and sensory disabilities. Starting with a brief overview on the importance of the qualitative method in the study of disability, and on the use of some qualitative research techniques applied to this context, The article intends to highlight how, in some cases, qualitative interviews can provide better results than other techniques. Nevertheless, some difficulties can emerge also using qualitative interviews, in particular with deaf people. Moreover, since the research team included a disabled researcher, the article describes some problems that the latter (but not only) faced during the research.